Delegation and Coordination with Multiple Threshold Public Goods: Experimental Evidence - Luca Corazzini; Christopher Cotton; Tommaso G. Reggiani (Institute of Labor Economics (IZA), 2019)
When multiple charities, social programs and community projects simultaneously vie for funding, donors risk miscoordinating their contributions leading to an inefficient distribution of funding across projects. Community chests and other intermediary organizations facilitate coordination among donors and reduce such risks. To study this, we extend a threshold public goods framework to allow donors to contribute through an intermediary rather than directly to the public goods. Through a series of experiments, we show that the presence of an intermediary increases public good success and subjects' earnings only when the intermediary is formally committed to direct donations to socially beneficial goods. Without such a restriction, the presence of an intermediary has a negative impact, complicating the donation environment, decreasing contributions and public good success.
Keywords: C91; C92; H40; H41; L31; 330; delegation; threshold public goods; laboratory experiment; fundraising